Integrating Canva and Assemblr Studio for Interactive Media in Teaching Descriptive Text Writing at the Junior High School Level - Witty Fadhila; Nursaid Nursaid (AL-ISHLAH: Jurnal Pendidikan, 2025)
In Indonesia’s Merdeka Curriculum, which emphasizes student-centered and technology-integrated learning, junior high school students often struggle with descriptive text writing due to limited visualization and engagement. Traditional methods fall short in supporting the development of observational and expressive writing skills. This study employed a Research and Development (RD) design using the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation—to create an interactive digital learning tool. The tool integrated Canva Site for instructional design and Assemblr Studio Web for augmented reality (AR)-based 3D object visualization. The product underwent expert validation (media, linguistic, and instructional) and was tested on 21 eighth-grade students to assess practicality and effectiveness. Validation scores indicated high quality: 96% (media), 80% (language), and 95% (instruction). Practicality testing yielded a 90.53% acceptance rate, showing strong usability and engagement. A paired sample t-test revealed a statistically significant improvement in students' descriptive writing performance (p = 0.000), demonstrating the tool’s effectiveness in enhancing writing outcomes. The integration of visual and AR elements supported multimodal learning and stimulated richer descriptions, aligning with Mayer’s multimedia learning theory and Vygotsky’s sociocultural framework. This approach also reinforced the goals of the Merdeka Curriculum by promoting creativity, critical thinking, and digital literacy. The study presents a valid, practical, and effective model for integrating Canva and Assemblr in language instruction, offering a replicable solution to improve descriptive writing skills through immersive digital media.